Multi-faceted proteomic characterization of host protein complement of Rift Valley fever virus virions and identification of specific heat shock proteins, including HSP90, as important viral host factors. - Jonathan E Nuss; Kylene Kehn-Hall; Ashwini Benedict; Julie Costantino; Michael Ward; Brian D Peyser; Cary J Retterer; Lyal E Tressler; Laura M Wanner; Hugh F McGovern; Anum Zaidi; Scott M Anthony; et al. (PLoS ONE, 2014)
Rift Valley fever is a potentially fatal disease of humans and domestic animals caused by Rift Valley fever virus (RVFV). Infection with RVFV in ruminants can cause near 100% abortion rates and recent outbreaks in naïve human populations have suggested case fatality rates of greater than thirty percent. To elucidate the roles that host proteins play during RVFV infection, proteomic analysis of RVFV virions was conducted using complementary analytical approaches, followed by functional validation studies of select identified host factors. Coupling the more traditional Gel LC/MS/MS approach (SDS PAGE followed by liquid chromatography tandem mass spectrometry) with an alternative technique that preserves protein complexes allowed the protein complement of these viral particles to be thoroughly examined. In addition to viral proteins present within the virions and virion-associated host proteins, multiple macromolecular complexes were identified. Bioinformatic analysis showed that host chaperones were among over-represented protein families associated with virions, and functional experiments using siRNA gene silencing and small molecule inhibitors identified several of these heat shock proteins, including heat shock protein 90 (HSP90), as important viral host factors. Further analysis indicated that HSP inhibition effects occur during the replication/transcription phase of the virus life cycle, leading to significant lowering of viral titers without compromising the functional capacity of released virions. Overall, these studies provide much needed further insight into interactions between RVFV and host cells, increasing our understanding of the infection process and suggesting novel strategies for anti-viral development. In particular, considering that several HSP90 inhibitors have been advancing through clinical trials for cancer treatment, these results also highlight the exciting potential of repurposing HSP90 inhibitors to treat RVF.